2012
DOI: 10.1021/jf2052256
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the Identity of the Main Ellagitannin in the Fruit of the Strawberry, Fragaria vesca and Fragaria ananassa Duch.

Abstract: Although the composition of strawberry fruit has been extensively studied, especially for the most abundant phenolic compounds, agrimoniin has never been univocally identified as one of the most abundant phenolic compounds in the fruit. In this study agrimoniin was isolated in the fruit of Fragaria vesca and its structure characterized. Furthermore, its presence was definitively established to be the main ellagitannin in both F. vesca and Fragaria ananassa D. fruit. The presence of sanguiin H-6 and lambert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 30 publications
12
76
1
Order By: Relevance
“…Laevigatins have originally been identified from Rosa laevigata (Yoshida et al, 1989a(Yoshida et al, , 1989b, but based on the structural characteristics which laevigatins have with agrimoniin (monomers are glucopyranosebased and the linkage between two monomers comprising the corresponding dimer is m-GOG group), it is possible that laevigatins are present in the studied plant species. We were not able to detect sanguiin H-6 (43) or lambertianin C (53) from strawberry (nor from any other of the Potentilla, Alchemilla or Comarum) samples, although previously such observations have been reported (Gasperotti et al, 2013;Vrhovsek et al, 2012). Monomeric ETs were only found in trace amounts and included compounds such as pedunculagin (1), tellimagrandin I (2), isostrictinin (6) (also its isomer 7) and possibly agrimonic acid A/B (28/29) (Yoshida et al, 1989a(Yoshida et al, , 1989b.…”
Section: -31contrasting
confidence: 57%
“…Laevigatins have originally been identified from Rosa laevigata (Yoshida et al, 1989a(Yoshida et al, , 1989b, but based on the structural characteristics which laevigatins have with agrimoniin (monomers are glucopyranosebased and the linkage between two monomers comprising the corresponding dimer is m-GOG group), it is possible that laevigatins are present in the studied plant species. We were not able to detect sanguiin H-6 (43) or lambertianin C (53) from strawberry (nor from any other of the Potentilla, Alchemilla or Comarum) samples, although previously such observations have been reported (Gasperotti et al, 2013;Vrhovsek et al, 2012). Monomeric ETs were only found in trace amounts and included compounds such as pedunculagin (1), tellimagrandin I (2), isostrictinin (6) (also its isomer 7) and possibly agrimonic acid A/B (28/29) (Yoshida et al, 1989a(Yoshida et al, , 1989b.…”
Section: -31contrasting
confidence: 57%
“…This wide range may be due to the juice production conditions, including the dose and type of enzyme and the intensity of pulp pressing and extraction, which usually depend on the price and availability of the raw material. The average energy value of 100 g of dried industrial strawberry press cake calculated on the basis of the content of proteins, fats, dietary fiber, and carbohydrates in accordance with the Commission Directive 2008/100/EC amounts to 309 kcal/100 g and is almost 10 times higher than the energy value of strawberry Assignments based on Vrhovsek U. et al [14] fruits (32 kcal/100 g) [2,38]. This results from the fact that water is removed from press cake, as opposed to proteins and fats.…”
Section: Resultsmentioning
confidence: 89%
“…The 1 H NMR assignments for both substances are identical, which confirm agrimoniin to be the main strawberry ellagitannin. The zoom of NMR spectrum of agrimoniin (at the same range as presented by Vrhovsek et al [14]) is shown on Fig. 1.…”
Section: Nmr Analysis Of Agrimoniinmentioning
confidence: 86%
See 2 more Smart Citations